2014
DOI: 10.1017/s1474747214000249
|View full text |Cite
|
Sign up to set email alerts
|

Discretion in the accounting for defined benefit obligations – an empirical analysis of German IFRS statements

Abstract: Following the research approach of Hann et al. (2007), this study investigates how discretion in the determination of the defined benefit obligation (DBO) is perceived by investors using a sample of listed German companies in the period of 2005–2011. For this, actuarial assumptions – discount interest rates, compensation growth rate and projected future pension increases – are replaced by their respective industry medians to obtain that component of the DBO, which can be attributed to discretion. We find that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…They also report that the R 2 figure obtained by using only net income is greater than the R 2 figure obtained by using only discounted cash flow estimates while the R 2 figure obtained by using only BVE is quite negligible . Salewski and Zülch () study the VR of the discretionary part of the defined benefit obligation and report that this item is not value relevant at conventional significance levels. Salewski and Zülch () also divide their sample into two and reveal that this item is value relevant only for the underfunded sample.…”
Section: Selected Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…They also report that the R 2 figure obtained by using only net income is greater than the R 2 figure obtained by using only discounted cash flow estimates while the R 2 figure obtained by using only BVE is quite negligible . Salewski and Zülch () study the VR of the discretionary part of the defined benefit obligation and report that this item is not value relevant at conventional significance levels. Salewski and Zülch () also divide their sample into two and reveal that this item is value relevant only for the underfunded sample.…”
Section: Selected Literaturementioning
confidence: 99%
“…Salewski and Zülch () study the VR of the discretionary part of the defined benefit obligation and report that this item is not value relevant at conventional significance levels. Salewski and Zülch () also divide their sample into two and reveal that this item is value relevant only for the underfunded sample.…”
Section: Selected Literaturementioning
confidence: 99%
“…This finding is consistent with a previous study where uniformity in accounting practice was found to be associated with IFRS non-adoption. For example, Salewski and Zülch (2015) reported that German listed companies were challenged by the lack of uniformity in IAS 19. The companies were found to be resistant to changes from the GAAP accounting regime to IFRS.…”
Section: International Journal Of Accounting and Financial Reportingmentioning
confidence: 99%
“…Using data available in the notes of most company accounts we create an alternative value of liabilities based on 'risk-free' (government bond yield) discounting and compare the market impact of pension decits/surpluses based on that measure as compared with the published measure. In doing so we link to a stream of the literature that adjusts reported pension liabilities to a common basis to make them comparable (Asthana, 1999;Hann et al, 2007b;Salewski and Zülch, 2015;Billings et al, 2017), with an important dierence: while most of the previous literature standardises actuarial assumptions to industry medians, we can use the unique features of UK data to recover the duration of pension liabilities for each company and thus use the appropriate risk-free rate to discount them.…”
Section: Introductionmentioning
confidence: 99%
“…Our paper provides an empirical contribution to that debate, showing that equity investors in UK companies value DB pension commitments using risk-free discounting. In estimating pension liabilities with a different rate from that used in the published accounts, we link to a stream of the literature that adjusts reported pension liabilities to a common basis to make them comparable (Asthana, 1999;Billings et al, 2017;Salewski & Zülch, 2015), with an important difference: while most of the previous literature standardises actuarial assumptions to industry medians, we can use the unique features of UK data to recover the duration of pension liabilities for each company and, thus, use the appropriate risk-free rate to discount them. 5 We find that only in the case of risk-free discounting are our estimates consistent with the prediction that a £1 increase in the tax-adjusted deficit has a £1 impact on the value of the T A B L E 1 DB pension facts This table reports statistics on defined benefit (DB) pensions in the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%